Impact of Lockdown On College Students Sleep Quality, Physical Activity and Eating Attitudes in South India—A Cross-Sectional Observational Study: Life Sciences-Medical Physiology - Periasamy, Panneerselvam; Ansar, Shajahan; Suganthi, Vajiravelu; Gunasekaran, Sasikala; Vaithilingam, Krishnakumar; Kannan, Velu Rajesh (International Journal of Life Science and Pharma Research, 2022)
The COVID-19 pandemic has forced the public health authorities to impose a lockdown as an epidemiological containment strategy. Due to COVID-19, the world is facing an unprecedented challenge that has changed people’s lifestyles. This study aimed to evaluate how the COVID-19 pandemic lockdown affected students in Tamilnadu in terms of changes to their eating habits, sleeping patterns, and level of physical activity. A cross-sectional study was conducted using a random representative sample of 263 undergraduate students (mean age 19.63+1.86 years, males 33.46%) from Tamilnadu voluntarily filling out an online questionnaire. The Pittsburgh Sleep Quality Index (PSQI) and The International Physical Activity Questionnaires, Eating Attitude Test (EAT-26) were used to assess sleep quality, Physical Activity, and Eating Attitude disorder, respectively. The prevalence of poor sleep quality among participants was 43.3% (males: 44.32% and females: 42.86%). The mean score of the participants’ EAT-26 score was found to be 10.92 ± 8.63. Students’ high body weight and BMI risk factors for eating disorders (2=9.68 p=0.02, 2=9.59 p=0.02). 46% of students did not do any physical activity. There is no significant correlation between sleep and Eating attitude scores (p=0.21). 66.16% of participants experienced Psychological stress due to lock down. Findings from this study indicate that a lockdown period due to COVID-19 negatively impacted young undergraduate adults’ physical activity levels and sleep quality. Finally, body weight, BMI, monthly family income, and poor physical activity with excess eating during the COVID 19 lockdown were the common exposures that are significantly associated with a higher risk of developing sleep disturbances and eating disorders. Several efficient strategies, programs, and coordinated efforts must be rigorously executed to encourage a seamless transition between school and daily life.